Comparisons of pharmacokinetic parameters of valproic acid between responsive and resistant adult epileptic - Panomvana, Duangchit; Boonmark, Lakkana; Sriboonruang, Tatta; Towanabut, Somchai (Chulalongkorn Medical Journal, 2023)
Objectives : To determine whether there are valproic acid (VPA) pharmacokinetic (PK) parameters differences between the VPA-responsive and VPA-resistant patient groups. Methods : Thirty-three subjects (14 patients were in VPA-resistant group and 19 patients in VPA-responsive group) who were epileptic patients were recruited from the Neurology Clinic, Neurology Institute, Bangkok. Their ages were 15 - 65 years old. They were either treated with VPA (Depakine Chrono) monotherapy or polytherapy in which the combined drug did not have the same metabolic pathways as VPA. At steady state condition, two blood samples were collected from the subjects during elimination phase, approximately five hours apart. Individual PK parameter values of VPA were estimated using the equations for a linear one-compartment model with a first-order declining of drug concentration after the end of 14 hours zero-order drug release. Chi-square test and the odds ratio were used to analize the data. Results : Under steady state condition after consuming Depakine Chrono®, a volume of distribution value (Vd) obtained from total VPA concentrations was statistically significantly different between two patient groups (p<0.05). Additionally, Vd value of total VPA less than 0.3 l/kg was associated with nonresponsive to VPA treatment (p<0.05). While, half life (t ½ ) of total VPA less than 25 hours and parameters obtained from unbound VPA concentrations such as Vd value less than 0.7 l/kg and t½ less than 10 hours had higher tendency to belong to the VPA-resistant group but they did not reach statistical significance (p>0.05); however, all these parameters were taken significant when p <0.1. Conclusions : The PK parameter values estimated from two blood samples collected during the routine clinical therapeutic drug monitoring might be used to identify whether or not the epileptic patient responds to the VPA therapy and thus could reduce the steps of trial and error.